Softwarelokalisierung - ein neues Arbeitsfeld für Übersetzerinnen und Übersetzer - Schmitz, Klaus-Dirk (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Internationalization and localization are keywords in our present global economy. The Development and marketing of products and services are successful only if they can be adapted to requirements of the target market in a fast and easy way. The adaptation of software products that are linguistically, culturally, legally and technically appropriate for a regional market is called software localization. This paper gives an overview of the field of software localization. After some general definitions of important concepts, the types of “texts” that have to be localized and the types of software tools that are used for localization are described. Special linguistic and non-linguistic aspects relevant and specific to localization in general are discussed and explained using examples.